2022
DOI: 10.4166/kjg.2021.139
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hepatic Neuroendocrine Tumor Arising at a Young Age: Rare Case Report and Literature Review

Abstract: Neuroendocrine tumors (NETs) are low-grade malignancies arising from neuroendocrine cells. Primary hepatic neuroendocrine tumors (PHNETs) are extremely rare and difficult to differentiate from other liver tumors, such as hepatocellular carcinoma (HCC) or cholangiocarcinoma. A 22-year-old male presented with intermittent abdominal pain. A preoperative imaging study revealed a 5.1cm-sized heterogeneously enhancing mass in S6 of the liver, suggesting HCC. Laparoscopic right hepatectomy was performed, and a well-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The size of the tumor is 1.5–27 cm, presenting as single (76.3%) and multiple in 23.7% of cases, located mainly in the right lobe in 48.4% of cases, and as bilobular in 18.5%. Knox et al [54] reported extrahepatic involvement in 18.6% of cases, such as bone (60%), lymph node (60%), and lung (40%) [9‒55]. The form of tumor presentation was two liver tumors that occupied both lobes of approximately 20 cm with metastasis to the mesentery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the tumor is 1.5–27 cm, presenting as single (76.3%) and multiple in 23.7% of cases, located mainly in the right lobe in 48.4% of cases, and as bilobular in 18.5%. Knox et al [54] reported extrahepatic involvement in 18.6% of cases, such as bone (60%), lymph node (60%), and lung (40%) [9‒55]. The form of tumor presentation was two liver tumors that occupied both lobes of approximately 20 cm with metastasis to the mesentery.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for RFA are the presence of three or fewer tumors and a tumor diameter of ≤5 cm. Tumors located near the major branches of the portal and hepatic veins have a higher potential for incomplete ablation [ 10 , 55 , 56 ]. Approximately 20–37% of patients are diagnosed at the metastatic or advanced stage, where platinum-based chemotherapy (etoposide + cisplatin [EP] or carboplatin [EC]) is the first-line treatment according to The European Society for Medical Oncology (ESMO) guideline [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a different investigation revealed that 83.3% of PHNETs displayed mixed echogenicity, and suggested that cystic changes frequently occur in PHNETs ( 8 ). Therefore, cystic change may represent a feature of PHNETs ( 19 ), although this requires confirmation in a larger cohort. Occasionally, calcifications (21.4%) were also present in PHNETs, which is different from NBNC-HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate Cox analysis in this study showed that older age (>76 years), neuroendocrine carcinoma, and chemotherapy treatment predicted poorer OS and DSS, while surgery predicted better OS and DSS. It is known that a PHNET is generally diagnosed at an older age ( 21 ); however, a case of a PHNET that occurred at a young age, which was misdiagnosed as hepatocellular carcinoma preoperatively, was reported in South Korea ( 22 ). This report was consistent with our results that age is an independent risk factor affecting the prognosis of patients with PHNETs.…”
Section: Discussionmentioning
confidence: 99%